Use of GA3 toincrease bunch size in crop forced table grapes - Pacheco, Daniela; Pugliese, Maria Beatriz; Infante, Silvina; Mundaca, Sergio Abel; Morales, Omar Alberto; Aballay, José Daniel (Sociedad Argentina de Fisiología Vegetal, 2026)
Poster de la presentación